Realizing Islam, Sustainable History Monograph Pilot OA Edition The Tijaniyya in North Africa and the Eighteenth-Century Muslim World - Valentine Wright, Zachary (The University of North Carolina Press, 2020)
The Tijaniyya is the largest Sufi order in West and North Africa. In this unprecedented analysis of the Tijaniyya's origins and development in the late eighteenth century, Zachary Valentine Wright situates the order within the broader intellectual history of Islam in the early modern period. Introducing the group's founder, Ahmad al-Tijani (1737-1815), Wright focuses on the wider network in which al-Tijani traveled, revealing it as a veritable global Islamic revival whose scholars commanded large followings, shared key ideas, and produced literature read widely throughout the Muslim world. They were linked through chains of knowledge transmission from which emerged vibrant discourses of renewal in the face of perceived social and political corruption.